Regional Cardiac Needs - Africa: How to Heal the Global South - Yankah, Charles (Journal of Humanitarian Cardiovascular Medicine, 2025)
Background: The current population of Africa of 1.4 billion will double by 2050. Similarly the pediatric (43%: 387,6 million, < 15 yrs old) as the student age (< 25 years) population (60% : 884 millIion) will double. About 1- 4% of babies are born with congenital heart disease and 1-30% are susceptible to develop preventable rheumatic heart disease caused by streptococcal throat infection associated with rheumatic fever. Only 2% (0.5-3.4%) of children with heart diseases have access to heart surgery. Open heart surgery per million population in sub-Saharan Africa is 5/million as compared to 116/ million in South America, WHO recommends 400 OHS/million which is currently impossible in Africa even the 40 OHS/million suggested by PASCaTS remains unmet.